An Analysis of Application of Multiple Comparison Tests (Post-Hoc) In ANOVA In Recently Published Medical Research Literature - Swati Patel; Vipin Naik; Prakash Patel (National Journal of Community Medicine, 2015)
Background: The usage of statistical methods specially ANOVA and post hoc test are increase in medical research, however inaccurate application of ANOVA and post hoc test were observed commonly. So we reviewed application of ANOVA and post-hoc test in recent published biomedical research literature.